2017
DOI: 10.1016/j.annepidem.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Participation in a US community-based cardiovascular health study: investigating nonrandom selection effects related to employment, perceived stress, work-related stress, and family caregiving

Abstract: Background Participation in health studies may be inversely associated with employment and stress. We investigated whether employment, perceived stress, work-related stress, and family caregiving were related to participation in a longitudinal US community-based health study of black and white men and women aged ≥45 years. Methods Prevalence ratios and confidence intervals were estimated for completion of the second-stage (S2) of a two-stage enrollment process by employment (status, type), and stress (percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Since the 1980s, a number of studies have found that the multiple, competing demands of employment and family caregiving often impede one or both of these roles (Barling, MacEwen, Kelloway, & Higginbottom, 1994;Scharlach, 1994;Scharlach, Sobel, & Roberts, 1991;Schulz & Martire, 2009;Stephens & Frank, 2009;Stone & Short, 1990;Thrasher, Zabel, Wynne, & Baltes, 2015;Wagner, 2006). Several recent studies have continued to shed light on the effects of employment on care-related stress and work (Carr et al, 2018;DePasquale, Polenick, Davis, Berkman, & Cabot, 2018;DePasquale, Polenick, Davis, Moen, et al, 2017;Fekete, Siegrist, Tough, & Brinkhof, 2018;Lerner et al, 2017;MacDonald, Fujishiro, Howard, Landsbergis, & Hein, 2017;Oldenkamp et al, 2018;Paulson, Bassett, Kitsmiller, Luther, & Conner, 2017). Family caregiving can also affect employers.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1980s, a number of studies have found that the multiple, competing demands of employment and family caregiving often impede one or both of these roles (Barling, MacEwen, Kelloway, & Higginbottom, 1994;Scharlach, 1994;Scharlach, Sobel, & Roberts, 1991;Schulz & Martire, 2009;Stephens & Frank, 2009;Stone & Short, 1990;Thrasher, Zabel, Wynne, & Baltes, 2015;Wagner, 2006). Several recent studies have continued to shed light on the effects of employment on care-related stress and work (Carr et al, 2018;DePasquale, Polenick, Davis, Berkman, & Cabot, 2018;DePasquale, Polenick, Davis, Moen, et al, 2017;Fekete, Siegrist, Tough, & Brinkhof, 2018;Lerner et al, 2017;MacDonald, Fujishiro, Howard, Landsbergis, & Hein, 2017;Oldenkamp et al, 2018;Paulson, Bassett, Kitsmiller, Luther, & Conner, 2017). Family caregiving can also affect employers.…”
Section: Introductionmentioning
confidence: 99%
“…First, we only focused on participants with reported longest‐held jobs, not their entire occupational history. Our sample within the REGARDS cohort is likely biased toward self‐employed individuals as reported by Macdonald et al 53 Second, in the within‐occupation analysis, some occupations had small sample sizes which limit our level of confidence in their estimates. The small sample sizes also prevented us to perform the adjustment in some occupation groups which we noted in the footnotes and impact the interpretation of the results in those groups.…”
Section: Discussionmentioning
confidence: 94%